Continuous architecture in practice : software architecture in the age of agility and DevOps - Erder, Murat; Pureur, Pierre; Woods, Eoin (1 St ed, 2021)
Authors Murat Erder, Pierre Pureur, and Eoin Woods have taken their extensive software architecture experience and applied it to the practical aspects of software architecture in real-world environments. Continuous Architecture in Practice provides hands-on advice for leveraging the continuous architecture approach in real-world environments and illuminates architectures changing role in the age of Agile, DevOps, and cloud platforms. This guide will help technologists update their architecture practice for new software challenges. As part of the Vaughn Vernon Signature Series, this title was hand-selected for the practical, delivery-oriented knowledge that architects and software engineers can quickly apply. It includes in-depth guidance for addressing today's key quality attributes and cross-cutting concerns such as security, performance, scalability, resilience, data, and emerging technologies. Each key technique is demonstrated through a start-to-finish case study reflecting the authors deep experience with complex software environments. -- Provided by publisher.
Foreword by Vaughn Vernon, Series Editor -- Foreword by Kurt Bittner -- Introduction -- Acknowledgments -- About the Authors -- Why Software Architecture Is More Important than Ever -- Architecture in Practice: Essential Activities -- Data Architecture -- Security as an Architectural Concern -- Scalability as an Architectural Concern -- Performance as an Architectural Concern -- Resilience as an Architectural Concern -- Software Architecture and Emerging Technologies -- Conclusion -- Appendix A: Case Study -- Appendix B: Comparison of Technical Implementations of Shared Ledgers
Includes bibliographical references and index.
Keywords: Software architecture; Architecture logicielle; Software architecture